The effect of the Great Recession on health: A longitudinal study of Irish mothers 2001-2011 - Jonathan Briody; Orla Doyle; Cecily Kelleher (University College Dublin, UCD Centre for Economic Research, 2019)
The relationship between recessions and health is mixed, with some evidence from the most recent financial crisis finding a positive effect on heath behaviours. This study uses longitudinal data spanning the periods before, during and after the Irish crisis of 2008, to test the impact of economic expansion and contraction on mothers physical and mental health and health behaviours. Three waves of data from the Irish Lifeways Cohort Study for the period 2001-2011, and local area employment rates from the Irish Census, are used to capture the impact of the recession on health, independent of individual employment status. The results from fixed effect linear probability models demonstrate that increases in the local unemployment rate are associated with significant increases in the probability of mothers reporting poor self-rated health and poor mental well-being. Yet the association between local area unemployment and health behaviours is mostly positive, with higher unemployment reducing the probability of being obese and tobacco consumption. The relationship with physical activity is more ambiguous. These results are largely consistent with the US literature, which is predominantly based on working men, thus demonstrating the universal impact of recessions on health.
Keywords: I10; I12; I14; I18; C33; J10; 330; Lifestyles; Health; Macroeconomic conditions; Panel data; Unemployment; The Great Recession